Genetic diversity among landraces of cucumber (Cucumis sativus L.) from north east India (Bangladesh Journal of Botany, 2019)
Twenty eight diverse landraces collected from various parts of North Eastern Region of India along with two checks were evaluated to study the diversity pattern among the genotypes on 17 morphological traits. High magnitude of genotypic coefficients of variation (GCV) and heritability coupled with high genetic gain were observed for average fruit weight, fruit yield per plant, number of fruits per plant, fruit length, number of branches per plant, number of seeds per fruit and 100 seed weight. However, these parameters were moderate for early fruit harvest and total soluble solids (TSS). Thirty genotypes were grouped into 6 clusters which showed intercluster D2 values ranging between 115.81 and 670.08. Grouping of genotypes of same location in different clusters indicated that the geographical diversity may not necessarily be related to genetic diversity. The cumulative contribution (82.28%) of fruit weight, 100-seed weight, number of branches per plant and fruit yield per plant to the total divergence indicate the importance of these traits in choice of parents for hybridization programme in cucumber.